Identifying and characterising PPE7 (Rv0354c) high activity binding peptides and their role in inhibiting cell invasion (2017)
This study was aimed at characterising the PPE7 protein from the PE/PPE protein family. The presence and transcription of the rv0354c gene in the Mycobacterium tuberculosis complex was determined and the subcellular localisation of the PPE7 protein on mycobacterial membrane was confirmed by immunoelectron microscope. Two peptides were identified as having high binding activity (HABPs) and were tested in vitro regarding the invasion of Mycobacterium tuberculosis H37Rv. HABP 39224 inhibited invasion in A549 epithelial cells and U937 macrophages by more than 50%, whilst HABP 39225 inhibited invasion by 40% in U937 cells. HABP 39224, located in the protein’s C-terminal region, has a completely conserved amino acid sequence in M. tuberculosis complex species and could be selected as a base peptide when designing a subunit-based, anti-tuberculosis vaccine. © 2017, Springer Science+Business Media New York.